College Adjustment among Bachelor Students: Multidimensional Relationship with Home, Health, Emotion, Social, and Educational Factors - Maharjan, Rocky (The Batuk, 2023)
The successful adjustment of bachelor students to college life affects their academic achievement, personal development, and overall well-being. The purpose of this study was to look into the effects of home, health, emotional, social, and educational factors on college adjustment among Nepalese bachelor's degree students. A structured questionnaire survey was completed by 178 undergraduates from various Nepalese colleges. Results showed that, home-related factors, physical health, emotional factors, social support, and academic support all had a significant relationship on college adjustment. Furthermore, gender differences were not observed, the level of college adjustment found to be average and unsatisfactory irrespective of gender, emphasizing the importance of individualized interventions. The study adds to our understanding of the factors that relates college adaptation and provides insights for designing effective support systems to help Nepalese bachelor students successfully transition into college life.